ISSUES OF VALUATION OF INVENTORIES IN ACCOUNTING - Khayitboyev Myxammadi Israpilovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article describes the nature of inventories, their evaluation according to international standards and the procedure for disclosing them in financial statements.